Disease-free Pre-Basic Seed Potato Production through Tissue Culture in Nepal - Sakha, Binesh M.; Rai, Gyan P.; Dhital, Shambhu P.; Nepal, Ram B. (Nepal Agriculture Research Journal, 2014)
Pre-basic seed potatoes are disease free potato minitubers produced by transplanting pathogen free in vitro potato plantlets under protected condition in aphid-proof glasshouse and/or screen house. Double antibody sand witched - enzyme linked immuno-sorbant assay is used to test six major potato viruses, namely PLRV, PVS, PVX, PVY, PVA and PVM. Thermotherapy cum meristem tip excision techniques are used to eliminate these viruses. Virus free in vitro potato plantlets are rapidly propagated by single nodal cuttings on modified MS media. For pre-basic seed production disease free in vitro potato plantlets are transplanted in the sterile sand soil substrate under glasshouse and screen house, once in autumn season and next in spring season. Since 1990, National Potato Research Program has been producing about 200,000 pre-basic seeds annually. So far, PBS of 19 different recommended and released potato cultivars has been produced. Till date 3,465,799 PBS had been produced and 3,217,666 pre-basic seeds distributed to the different seed potato growers groups, District Agriculture Development Offices, government farms/research stations, and NGOs/INGOs for subsequent basic seed potato production. After establishment of tissue culture facilities in National Potato Research Program, the productivity of potato has been increased by 71% due to utilization of pre-basic seed potatoes. Nepal Agric. Res. J. Vol. 8, 2007, pp. 7-13 DOI: http://dx.doi.org/10.3126/narj.v8i0.11564